2019
DOI: 10.1007/s40430-019-1947-9
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of uncertainty in free vibration of Euler–Bernoulli nanobeam

Abstract: In this paper, Euler-Bernoulli nanobeam based on the framework of Eringen's nonlocal theory is modeled with material uncertainties where the uncertainties are associated with mass density and Young's modulus in terms of fuzzy numbers. A particular type of imprecisely defined number, namely triangular fuzzy number, is taken into consideration. In this regard, double parametric-based Rayleigh-Ritz method has been developed to handle the uncertainties. Vibration characteristics have been investigated, and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Karayer et al [2] introduced the fractional method for some aspects of quantum mechanics. Jena et al [3] showed that the damping characteristics when solving the damped beam equation are well defined by the fractional derivative and solved the model of the large membrane vibration equation using Caputo derivatives. This description does not go into structure, but assumes a degree of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Karayer et al [2] introduced the fractional method for some aspects of quantum mechanics. Jena et al [3] showed that the damping characteristics when solving the damped beam equation are well defined by the fractional derivative and solved the model of the large membrane vibration equation using Caputo derivatives. This description does not go into structure, but assumes a degree of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%